Donepezil promotes differentiation of neural stem cells into mature oligodendrocytes at the expense of astrogenesis. Issue 2 (17th October 2016) - Imamura, Osamu; Arai, Masaaki; Dateki, Minori; Takishima, Kunio
Abstract: Oligodendrocytes are the myelin‐forming cells of the central nervous system. Oligodendrocyte loss and failure of myelin development result in serious human disorders, including multiple sclerosis. Previously, using oligodendrocyte progenitor cells, we have shown that donepezil, which is an acetylcholinesterase inhibitor developed for the treatment of Alzheimer's disease, stimulates myelin gene expression and oligodendrocyte differentiation. Here, we aimed to analyze the effects of donepezil on primary mouse embryonic neural stem cells (NSCs). Donepezil treatment led to impaired self‐renewal ability and increased apoptosis. These effects appeared to be mediated through the Akt/Bad signaling pathway. Using neurosphere differentiation analysis, we observed that donepezil leads to reduced numbers of astrocytes and increased numbers of oligodendrocytes and neurons. Consistent with this finding, mRNA and protein levels for the oligodendrocyte markers myelin‐associated glycoprotein, 2′, 3′‐cyclic‐nucleotide 3′‐phosphodiesterase (CNPase), and myelin basic protein, as well as the neuronal marker β‐tubulin type III (Tuj1) were up‐regulated. In contrast, the expression of the astrocyte marker glial fibrillary acidic protein (GFAP) was down‐regulated by donepezil in a dose‐ and time‐dependent manner. Moreover, donepezil increased oligodendrocyte differentiation, resulting in a reduction in the differentiation of NSCs into astrocytes, by suppressing the activation of signal transducer and activator of transcription 3 (STAT3), SMAD1/5/9, and the downstream target gene GFAP, even under astrocyte‐inducing conditions. These results suggest that efficient differentiation of NSCs into oligodendrocytes by donepezil may indicate a novel therapeutic role for this drug in promoting repair in demyelinated lesions in addition to its role in preventing astrogenesis. Abstract : Oligodendrocyte loss and failure of myelin development result in serious human disorders, including multiple sclerosis. We show that donepezil (DNP), a drug for the treatment of Alzheimer's disease, can stimulate the differentiation of neural stem cells (NSCs) into oligodendrocytes and neurons at the expense of astrogenesis. Moreover, DNP efficiently increases the numbers of mature oligodendrocytes and reduces astrocyte differentiation by suppressing the activation of the STAT and SMAD signaling pathways, which are key regulation pathways in the astrogenesis of NSCs.